Cantú Syndrome Is Caused by Mutations in ABCC9 - van Bon, Bregje W.M. (Elsevier, 2012)
Cantú syndrome is a rare disorder characterized by congenital hypertrichosis, neonatal macrosomia, a distinct osteochondrodysplasia, and cardiomegaly. Using an exome-sequencing approach applied to one proband-parent trio and three unrelated single cases, we identified heterozygous mutations in ABCC9 in all probands. With the inclusion of the remaining cohort of ten individuals with Cantú syndrome, a total of eleven mutations in ABCC9 were found. The de novo occurrence in all six simplex cases in our cohort substantiates the presence of a dominant disease mechanism. All mutations were missense, and several mutations affect Arg1154. This mutation hot spot lies within the second type 1 transmembrane region of this ATP-binding cassette transporter protein, which may suggest an activating mutation. ABCC9 encodes the sulfonylurea receptor (SUR) that forms ATP-sensitive potassium channels (K(ATP) channels) originally shown in cardiac, skeletal, and smooth muscle. Previously, loss-of-function mutations in this gene have been associated with idiopathic dilated cardiomyopathy type 10 (CMD10). These findings identify the genetic basis of Cantú syndrome and suggest that this is a new member of the potassium channelopathies.